Silibinin Improves TNF-α and M30 Expression and Histological Parameters in Rat Kidneys After Hepatic Ischemia/Reperfusion. (4th May 2018) - Kyriakopoulos, Georgios; Tsaroucha, Alexandra K.; Valsami, Georgia; Lambropoulou, Maria; Kostomitsopoulos, Nikolaos; Christodoulou, Eirini; Kakazanis, Zacharias; Anagnostopoulos, Constantinos; Tsalikidis, Christos; Simopoulos, Constantinos E.
ABSTRACT: Background : Remote kidney damage is a sequel of hepatic ischemia–reperfusion (I/R) injury. Silibinin is the main ingredient of the milk thistle plant seed extract with known antioxidant and hepatoprotective activity. Our study investigates the nephroprotective potential of intravenously administered silibinin, as a lyophilized SLB-hydoxypropyl-beta-cyclodextrin product, in hepatic I/R injury. Material and methods : 63 Wistar rats were divided into three groups: Sham (virtual intervention); Control (45 min ischemia and reperfusion); and Silibinin (200 μL intravenous silibinin administration after 45 min of ischemia). Kidney tissues were collected to determine TNF-α, M30 and histopathological changes at predetermined time intervals. Results : Comparing Sham vs. Control groups, proved that hepatic I/R injury increased renal TNF-α and M30 expression. Deterioration was observed in hyperemia/filtration of renal parenchyma and tubules, cortical filtration, tubular necrosis and edema (tissue swelling index). Intravenous silibinin administration and comparison of the Control vs. Silibinin groups showed a statistically significant decrease in TNF-α levels at 240 min following I/R ( p < 0.0001), and in M30 at 180 min ( p = 0.03) and 240 min ( p < 0.0001). Renal parameters have significantly decreased in: hyperemia/filtration of renal parenchyma at 120 min ( p = 0.003), 180 min ( p = 0.0001) and 240 min ( p = 0.0002); hyperemia/filtration of renal tubules at 120 min ( p = 0.02), 180 min ( p = 0.0001) and 240 min ( p = 0.0005); cortical filtration (240 min - p = 0.005); tubular necrosis (240 min - p = 0.021); and edema (240 min - p = 0.001). Conclusion : Our study confirms that hepatic I/R injury causes remote renal damage while the intravenous administration of silibinin leads to statistically significant nephroprotective action.